What Makes Conference Calls Useful? The Information Content of Managers' Presentations and Analysts' Discussion Sessions - Matsumoto, Dawn; Pronk, Maarten; Roelofsen, Erik (The Accounting Review, 2011)
ABSTRACT Conference calls held in conjunction with an earnings release have become increasingly common in recent years, yet there is little evidence regarding the reasons that these calls are incrementally informative over the accompanying press release. Using a sample of more than 10,000 conference-call transcripts, we examine the information content of both segments of the call—the presentation and the discussion segment. We find that both segments have incremental information content over the accompanying press release. However, discussion periods are relatively more informative than presentation periods, and this greater information content is positively associated with analyst following. We also find that managers provide increased disclosures during the presentation segment when firm performance is poor, but relatively more information is released during discussion periods in these circumstances. Overall, our results are consistent with the notion that active analyst involvement in conference calls increases the information content of the calls, particularly when firm performance is poor.